(untitled) (Global Journal of Management and Business Research, 2013)
The intention of this study is to determine the influence of social media towards generation Y purchasing behaviour. It is also to explore the important role social media play as a medium to communicate a message. The findings of this research are, intended to provide accurate and useful information so as to facilitate further research in similar fields of study. Permission was granted by the Directors of the IHLs to deliver and collect the questionnaires. Questionnaires were given to 200 students of ten selected institutions of higher learning in the Klang Valley. The respondents involved were students enrolled in the institute of higher learning. The respondents were asked about their perception with regards to its current social media website and how does it play a role in influencing their buying behaviour so as to gain their true interpretation and understanding of social media. Responses from the respondents have shown that, generally social media were used to gain information, prefer group buying and as a community platform to express and share their views.